Investigation for subchronic oral toxicity and evaluation of analgesic activities of Stephania tetrandra S. Moore liquid extract in experimental animals - Thanh Mai Phuong; Trang Tran Thi Thu; Khanh Do Thi Hong; Ngoc Tran Thi Hong; Dat Tran Tien; Trang Nguyen Thi Mai; Minh Phan Hong (Vietnam Journal of Science, Technology and Engineering, 2024)
This research evaluates subchronic toxicities and analgesic effects of Stephania tetrandra S. Moore (S. tetrandra) liquid extract through oral administration in experimental animals. Over 4 weeks of subchronic toxicity research, S. tetrandra was administered to Wistar rats at a dose of 1.6 g/kg body weight (BW) (the dose is equivalent to the expected human dose) and 4.8 g/kg BW (three times the human expected dose), based on World Health Organization (WHO) and Organisation for Economic Co-operation and Development (OECD) recommendations. The analgesic effect was assessed using three models: hot plate, tail-flick, and acetic acid-induced writhing in Swiss mice. Regarding the subchronic toxicity test, after oral administration of S. tetrandra liquid extract, haematological parameters, hepato-renal functions, and microscopic images of the liver and kidney were unchanged compared with the control group. As a result, S. tetrandra liquid extract at both doses of 3.2 g/kg/day and 9.6 g/kg/day tended to reduce pain in the models. The low dose significantly showed peripheral analgesic effects, while the high dose demonstrated better analgesic activity at both central and peripheral sites. In conclusion, S. tetrandra liquid extract did not produce subchronic toxicities in Wistar rats, and has shown experimental analgesic effects.